Training, Motivation, Job Satisfaction, And Employee Performance of CV Sido Agung - Fifi Andrea; Arif Murti Rozamuri (Indonesia Banking School, 2023)
This planning/research is about the effect of training, motivation, and job satisfaction on employee performance with the aim of knowing the effect of training, motivation, and job satisfaction on employee performance. The method used is quantitative. The research sample taken is the employee of CV Sido Agung. Data collection techniques using a questionnaire. The analysis used is descriptive analysis. The testing technique includes validity test, reliability test, classical assumption test in the form of normality test, hypothesis test in the form of t test, f test, and coefficient of determination test, multiple linear regression test. The results showed that : (1) There was no influence between training on employee performance, (2) There was no positive and significant effect between motivation on employee performance, (3) There was no positive and significant effect between job satisfaction on employee performance, (4) There is an influence between training, motivation, and job satisfaction on employee performance.